IMPLEMENTASI METODE PEMBELAJARAN TUTOR SEBAYA GUNA MENINGKATKAN HASIL BELAJAR SISWA SMK NU HASYIM ASYARI TARUB - Mukhamad Irpan Muzaqi (Universitas Negeri Yogyakarta, 2022)
This study aims to determine the average KKM and improve student learning outcomes in light vehicle engine maintenance subjects with peer tutoring methods in class XI TKR 6 at SMK NU Hasyim Asyari Tarub, this research method uses the type of classroom action research that was popularized and developed by Kemmis and Mc Taggart. The subjects of this study were 34 students of class XI TKR 6 even semesters of the 2020/2021 academic year. Data collection techniques in this study are by conducting observations, learning outcomes tests, and documentation on the research subject. The data analysis method used is descriptive. The results of the research in this classroom action research process are obtained data that by applying peer tutor learning methods on the subject of light vehicle engine maintenance in class XI TKR 6 SMK NU Hasyim Asyari Tarub there is an increase in learning outcomes, it is marked by an increase in the percentage of completeness student learning outcomes in each cycle. Student learning outcomes in the pre-cycle obtained the percentage of mastery learning outcomes of 52.94% then increased in the first cycle, with the obtained percentage of mastery learning outcomes of 76.47%. Cycle II experienced completeness learning outcomes of 79.41% and cycle II experienced learning completeness of 85.29%.